Визначення зони дії відкритих додатків для масивних вузлів у виливках з нержавіючої сталі - Шамрай, Андрій Вікторович; Мариненко, Дмитро Віталійович; Костик, Катерина Олександрівна; Кравцова, Наталія Вікторівна (НТУ "ХПІ", 2018)
Метою роботи є дослідження впливу розміру, форми та місце розташування додатків на утворення пористості у виливку за масивними вузлами із нержавіючою сталі. В ході роботи було спроектовано два найбільш поширених типу розташування масивного елементу на стінці виливка. На першому етапі було промодельовано процес кристалізації цих вузла у вільному стані, без додатків. Наявність пористості оцінювали за критеріям Ніяма. Наступним етапом було порівняно дію добутків, спроектованих за найбільш поширеними засобами розрахунку, та стандартних форм й розмірів. Для аналізу ефективності було проаналізовано поширення температурних полів та наявність пористості.

The main purpose of the app is receiving a suitable casting without shrinkage cavities and porosity. In general, the pattern of formation of these defects can be represented as follows: in a very short period of time on the casting surface and formed a crust of hardened alloy, which determines the outer contour of the casting; reduction of volume of the liquid metal inside the formed solid crust ahead of volumetric shrinkage, the most rigid sheath; in the absence of receipt of molten metal, which compensates the reduction of volume, voids are formed, called sinks, the size of which depends on the properties of the alloy, the temperature of the overheating and its original volume. The aim of this work is to study the influence of size, shape and location of applications on the formation of porosity in the casting behind the massive knots out of stainless steel. During the work was designed by the two most common type the location of the massive object on the wall of the casting. The first stage was simulated the crystallization process of these knots in the free state without application. The presence of porosity was evaluated according to the Niyama criterion. The next stage was a relatively action works, designed by the most common means of calculation, and standard shapes and sizes. For the analysis of efficiency was analyzed the distribution of temperature fields and the presence of porosity. The application must meet the following basic requirements: be sufficient to compensate for the shrinkage of the alloy during solidification; later hardening the casting parts to which it is attached; have the configuration (to keepmetal), which will provide a minimum cooling surface; area shrinkage should not go beyond the app and reach his neck.
Definition of range of open applications for massive nodes in the stainless steel castings
Keywords: моделювання; пористість; живлення; процес кристалізації; критерії Ніяма; application steel; simulation; risering